Current status of graft choice in adults for anterior cruciate ligament reconstruction: a systematic review and meta-analysis - Magadum, Mahantesh; Smith, Joshua; New, Karl J. (International Journal of Research in Orthopaedics, 2024)
The anterior cruciate ligament (ACL) is a frequently performed surgical procedure in the field of sports medicine, and graft selection is an essential aspect of ACL reconstruction (ACLR) that has been shown to optimize post-operative rehabilitation, facilitate return to full sporting function and reduce the risk of complications. However, there needs to be more agreement regarding optimal graft choice. The present study aims to identify the optimal graft choice in the adult population undergoing ACLR. The current systematic review explores the electronic database of online libraries of academic institutions from 2011 to 30 September 2022 and compared the clinical outcomes of autograft and allograft for ACLR, which provides an evidence-based approach for graft selection. The findings of our present study delineate that ACLR in adult populations with autograft is the most promising choice for ligament tear over allograft based on lower failure rate, reduced complications, and high cost-effectiveness. However, there was no significant difference in overall IKDC, pivot shift, Lachman test, and Tegner activity. This critical analysis recommends that for an adult population, ACLR with autograft can provide better clinical results than an allograft, but further studies carried out about other parameters affecting the long-term stability, quick return, and physical therapy adopted outside the supervision of the respective surgeon would be required.